Paradigma Organik-Integralistik dalam Ketatanegaraan: Analisis Perspektif Fikih Siyasah Kontemporer - Savitri Savitri; Asyifa Khairunnisa; Ribi Aulia; Maulagina Azkiya Mazidah; Riha Dhatul Aisyah; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The organic-integralistic paradigm in constitutional analysis views the nation and society as a whole interconnected unit. In the context of contemporary political jurisprudence, this paradigm is important to answer the complex challenges in the administration of modern government. This study aims to analyze the relevance of the organic-integralistic paradigm in the perspective of contemporary fiqh siyasah. The method used is qualitative research with a descriptive approach through literature study. The results of the study show that Islamic political thought developed in response to globalization, liberalism, and demands for the protection of people's rights. In this case, the organic-integralistic paradigm plays a role in building a constitutional system oriented to sharia maqashid. In addition, this paradigm encourages the creation of a harmonious relationship between religious values and state authority. Various implementation models were found, ranging from traditional religious approaches to organic-Islamic models that are adaptive to the times. Thus, the organic-integralistic paradigm can be a conceptual alternative in formulating an integrative constitutional system between religious norms and modern administrative principles in a balanced and sustainable manner.